2003
DOI: 10.1128/jb.185.14.4127-4135.2003
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Crystal Structure of the Multidomain Endoglucanase Cel9G from Clostridium cellulolyticum Complexed with Natural and Synthetic Cello-Oligosaccharides

Abstract: Complete cellulose degradation is the first step in the use of biomass as a source of renewable energy. To this end, the engineering of novel cellulase activity, the activity responsible for the hydrolysis of the ␤-1,4-glycosidic bonds in cellulose, is a topic of great interest. The high-resolution X-ray crystal structure of a multidomain endoglucanase from Clostridium cellulolyticum has been determined at a 1.6-Å resolution. The endoglucanase, Cel9G, is comprised of a family 9 catalytic domain attached to a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 42 publications
2
82
0
4
Order By: Relevance
“…The C. cellulolyticum and T. fusca proteins represent two types of family 9 theme B1 endoglucanases with the enzyme-cello-oligosaccharides cocrystal structures solved (36,45). The amino acid sequence alignment showed that most of the residues involved in cellulose substrate binding are well conserved in the GH9 module of CbCel9B/ Man5A (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. cellulolyticum and T. fusca proteins represent two types of family 9 theme B1 endoglucanases with the enzyme-cello-oligosaccharides cocrystal structures solved (36,45). The amino acid sequence alignment showed that most of the residues involved in cellulose substrate binding are well conserved in the GH9 module of CbCel9B/ Man5A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid sequences of the GH9 catalytic module of the Clostridium cellulolyticum Cel9G (GenBank accession number AAA73868) (36) and that of the Thermobifida fusca Cel9A (GenBank accession number AAB42155) (45) (38); and AAB42155, Cel9A of Thermobifida fusca (26,45). The aligned sequences were analyzed using BOXSHADE 3.21 (http: //www.ch.embnet.org/software/BOX_form.html) with a default setting of the fraction of sequences parameter as 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…The second group includes the structures of Cel9A from Alicyclobacillus acidocaldarius (AaCel9A) (3EZ8), 11 CelD from C. thermocellum (CtCelD) (1CLC), 12 and cellobiohydrolase CbhA from C. thermocellum (CtCbhA) (1UT9), 13 that contain an N-terminal immunoglobulin-like (Ig-like) domain besides the catalytic domain. The third group includes the structures of Cel9G from C. cellulolyticum (1G87) 14 and endo/exocellulase E4 from Thermomonospora fusca (1TF4) 15 that contain a C-terminal family 3 carbohydratebinding module (CBM3) besides the catalytic domain. The structures of the catalytic domains of these GH family 9 enzymes are characterized by the (a=a) 6 -barrel fold with three acidic active site residues (two aspartate and one glutamate residues).…”
Section: Introductionmentioning
confidence: 99%
“…18 LC-CelG is composed of 577 amino acid residues and contains a putative signal peptide (Residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] at the N-terminus. LC-CelG without this signal peptide consists of an N-terminal Ig-like domain (Residues 20-132) and a C-terminal catalytic domain (Residues 133-577).…”
Section: Introductionmentioning
confidence: 99%
“…This is not a unique observation for a glycoside hydrolase, but it is highly rare. The first example of a CBM contributing to the formation of a glycoside hydrolase active site was observed in GH9 endoglucanases, where a family 3c CBM, which is rigidly fused to the catalytic module, extends the active site along the binding face of the CBM (66,67). A more recent example is seen in the glycogen-degrading enzyme SpuA from Streptococcus pneumoniae, where the binding site of the CBM contributes to the formation of two additional active site subsites, allowing the recognition of glycogen branch points (68).…”
Section: Discussionmentioning
confidence: 99%